Social technology, local-based tourism and community-based tourism. Brief discussion seeking improvements in community tourism activities - Felipe Rosa, Thais (2023)
This work briefly analyses, the similarities between the theoretical concepts of the main authors who address the theories of Social Technology (ST), Local Based Tourism (LBT), and Community Based Tourism (CBT), in order to achieve a foundation from which new visions can be generated that reinforce local development in different communities dedicated to tourist activity, with a socio-environmental model different from those carried out through mass tourism. Part of the literary review used in the investigation of the double doctorate[1] is presented, based on the mentioned theoretical references. The analysis and the conclusions demonstrate the need to carry out more dialogues, approximations, and exchanges between these fields of knowledge, both in theory and in practice, in order to generate actions that imply the social inclusion of the less favored population, through logical, beneficial and sustainable tourist activities.   [1] Double Doctorate that arises from the agreement between the Program Interuniversitario de Turismo de la Universidad de Alicante, España and the Program em Ciência, Tecnologia e Sociedade. Universidade Federal de São Carlos, Brazil.